2022
DOI: 10.1039/d1nj06208e
|View full text |Cite
|
Sign up to set email alerts
|

An experimental and computational study of new spiro-barbituric acid pyrazoline scaffolds: restricted rotationvs.annular tautomerism

Abstract: A regioselective [3+2] cycloaddition (32CA) reaction to synthesize unsymmetric spiro-barbituric pyrazolines containing a chromone or phenolic pyrazole moiety was achieved, providing good to excellent yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…DFT calculations of spirobarbiturate scaffolds containing a locked phenolic pyrazole moiety demonstrated the predominance of restricted rotation about a single C-C bond over annular tautomerism. 63 A highly regioselective approach for preparing 4-bromo-7,9dimethyl-1-aryl-2-oxa-3,7,9-triazaspiro[4.5]dec-3-ene-6,8,10-trione derivatives was developed; it involved a 1,3-dipolar cycloaddition reaction between barbiturate-based olefins and nitrile oxide 25 by treatment with K 2 CO 3 in THF at room temperature. The dibromoformaldoximes, which are valuable reagents to synthesize nitrogen-and oxygen-containing heterocyclic compounds and can install multiple stereogenic centers with high atom economy through 1,3-dipolar cycloaddition, were prepared by using glyoxylic acid and hydroxylamine hydrochloride followed by bromination (Scheme 24).…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…DFT calculations of spirobarbiturate scaffolds containing a locked phenolic pyrazole moiety demonstrated the predominance of restricted rotation about a single C-C bond over annular tautomerism. 63 A highly regioselective approach for preparing 4-bromo-7,9dimethyl-1-aryl-2-oxa-3,7,9-triazaspiro[4.5]dec-3-ene-6,8,10-trione derivatives was developed; it involved a 1,3-dipolar cycloaddition reaction between barbiturate-based olefins and nitrile oxide 25 by treatment with K 2 CO 3 in THF at room temperature. The dibromoformaldoximes, which are valuable reagents to synthesize nitrogen-and oxygen-containing heterocyclic compounds and can install multiple stereogenic centers with high atom economy through 1,3-dipolar cycloaddition, were prepared by using glyoxylic acid and hydroxylamine hydrochloride followed by bromination (Scheme 24).…”
Section: Reviewmentioning
confidence: 99%
“…DFT calculations of spirobarbiturate scaffolds containing a locked phenolic pyrazole moiety demonstrated the predominance of restricted rotation about a single C–C bond over annular tautomerism. 63…”
Section: Synthesis Of Spirobarbituratesmentioning
confidence: 99%
“…The acetic acid-mediated synthesis involving Knoevenagel condensation of 3-formylchromone with 1,3-dimethylbarbituric acid in water is known. 23 We found that the resulting multifunctional synthon 1b could in situ react with ylidenemalononitrile 2b, which have been used extensively as vinylogous donors in Michael reactions. 24 Indeed, the chromonyl triene product containing barbiturate moiety 3b was obtained in a 65% yield within 24 hours.…”
mentioning
confidence: 93%